Distributional Effects of International Trade : Misconceptions about Losses and Gains - Artuc, Erhan (World Bank, Malaysia, 2021)
International trade increases efficiency but also redistributes income, thus creating winners and losers. To account for the total impact and calculate redistributive effects correctly and fully, the different channels of gains and losses must be measured precisely. This Brief shows that measuring the gains is often much more challenging than measuring the losses, generating misconceptions and an overstatement of the adverse impacts of international trade. To assess the effects of trade shocks objectively, and to promote effective policy options, policy makers must be aware of thelimitations in data and methodology surrounding the research on the distributional effects of international trade, and the misconceptions that ensue.